Ionization of 2‐ and 4(5)‐Nitroimidazoles Radiosensitizers: A "Kinetic Competition" Between NO2 and NO Losses. Issue 23 (12th October 2021) - Satta, Mauro; Casavola, Anna Rita; Cartoni, Antonella; Castrovilli, Mattea Carmen; Catone, Daniele; Chiarinelli, Jacopo; Borocci, Stefano; Avaldi, Lorenzo; Bolognesi, Paola
Abstract: Nitroimidazoles are a class of chemicals with a remarkable broad spectrum of applications from the production of explosives to the use as radiosensitizers in radiotherapy. The understanding of thedynamics of their fragmentation induced by ionizing sources is of fundamental interest. The goal of this work is to theoretically investigate the kinetic competition between the two most important decomposition channels of 2, 4 and 5‐Nitroimidazole cations: the NO and NO2 losses. The calculated rate constants of the two processes are in very good agreement with the experimental Photoelectron‐Photoion Coincidence (PEPICO) branching ratio. This study solves the intriguing and theoretically unexplained experimental observation that 2‐Nitroimidazole, at variance with the other two regio‐isomers is a source for only NO at low energies (<12.76 eV). This is a key point for biomedical application of the nitroimidazoles, because NO is the vasodilator that favors the reoxigenation of hypoxic tumor tissues. Abstract : The kinetic competition between the NO and NO2 loss channels in 2‐Nitroimidazole ions favours the former channel at low energies (<12.76 eV). Thus, at these energies, 2‐Nitroimidazole is an exclusive NO source, unlike 4 and 5‐Nitroimidazole isomers. This is important for biomedical applications since NO is a vasodilator that favors oxygenation of tissues.